Simulation of environmental impact of an existing natural gas dehydration plant using a combination of thermodynamic models - Torkmahalleh, Mehdi Amouei; Magazova, Galiya; Magazova, Aliya; Hassani Rad, Seyed Jamal (Process Safety and Environmental Protection, 2016)
A new approach was presented to improve the simulation results of an existing TEG based natural gas dehydration plant, using Aspen Plus software. Furthermore, the environmental impact of the plant was investigated. The plant consists of four main unit operations including an absorber, a flash tank, a stripper and a regenerator.
Keywords: Aspen Plus; BTEX; Greenhouse gas; Natural gas dehydration; Thermodynamic models; VOC; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics